Post-Cosecha y secado del grano del cacao nacional fino y de aroma para la determinación de perfiles físicos, bromatológicos y organolépticos - Bermúdez Albia, Kelvin Javier (2016)
This research was conducted in order to determine the physical, bromatológicos and organoleptic profiles from post-harvest processing and fine national cocoa aroma, the site "Tablada Sanchez" of the province of Manabí Chone Canton. The methodology used in this descriptive research was 5 days 4 days fermentation and drying solar radiation. The samples were obtained four farms producing fine national cocoa aroma and intercropping of wood, citrus, banana and cocoa. The variables evaluated to dry cocoa beans were: physical parameters (humidity percentage of fermentation and percentage of testa); bromatológicos (fat, pH, acidity and ash), and sensory cocoa liquor (basic tastes and flavors specific). The obtained results showed physical differences between the samples and the percentage of fermentation, which was between 70-90% of fermented grains; bromatological acidity and ash properties no greater variation between samples; contrary to pH fat and vary with respect to each sample. The profile basic flavors medium and high in bitterness, acidity and astringency levels was obtained, specific flavors showed major differences in the flavors of cocoa and fruity with respect to floral and nutty, these results serve as bank actual data qualities fine national cocoa and aroma that exist on the site "Sanchez Tablada", so start sorting by aroma and flavor cacao farms of canton Chone.